Ansiedade na performance musical e o papel do educador - Felipe Mancz (2018)
Through a questionnaire, this study gathered information concerning Projeto Guris (under Santa Marcelina Organizations management) voice and instrument teachers knowledge and perception about their students musical performance anxiety. The teachers answered what they knew about the subject and whether they perceived anxious students in classroom or during a concert. They answered that they had some knowledge about musical performance anxiety and that they find this situation among their students both in classes and in concerts. They also informed what strategies they used in order to cope with the students performance anxiety, in those cases when they decided to act against the situation